Virtual Laboratory in Chemistry: Recent Information and Communication Technologies (ICT) in Chemistry Practical Course - Imam Sahroni; Wiyogo Prio Wicaksono; Maisari Utami; Lutfia Isna Ardhayanti (IJCER (International Journal of Chemistry Education Research), 2020)
The covid-19 has impacted many sectors to change the way the run their activity, including the learning and teaching activity at a higher education. Many departments at the educational institution have been affected seriously due to the physical laboratory closing, especially for the activity at chemistry laboratory. The physical laboratory has been transformed to the virtual laboratory in order to accommodate the student to study the experimental course. By using the internet and communication technology (ICT) innovation in teaching and learning method, the student can still have the experiment and continue the lecture through online system. This effort may help the student to still play an active role while participating in the learning process.